Imepitoin Shows Benzodiazepine-Like Effects in Models of Anxiety - Engel, Odilo; Masic, Aleksandar; Landsberg, Gary; Brooks, Melissa; Mills, Daniel S.; Rundfeldt, Chris (Frontiers in Pharmacology, 2018)
Imepitoin is a low affinity partial agonist for the benzodiazepine binding site of γ–aminobutyric acid (GABAA) receptors, and is currently used as an antiepileptic in dogs. Here we tested imepitoin for anxiolytic properties. In an in vitro model, imepitoin was capable of preventing the effect of corticotrophin releasing factor (CRF) on locus coeruleus neurons without suppressing the basal activity of these cells, an activity which is suggestive for an anti-stress effect of imepitoin. In addition, we applied a battery of standard rodent preclinical tests for anxiety behaviour including elevated plus mazes in mice and rats, light-dark-box in mice and rats, social interaction test in rats, or the Vogel conflict test in rats. In all models, the observed profile of imepitoin appeared similar to benzodiazepines and typical for anxiolytic drugs. We also observed anxiolytic activity in dogs in a provoked open field sound-induced fear model, where reactions to noises were elicited by a sound recording of thunderstorms. Imepitoin caused an increase in locomotion measured in distance travelled and an ameliorating effect on cortisol levels in response to thunderstorm noises. For comparison, dexmedetomidine caused a decrease in locomotion and had no effect on cortisol. In all animal models the doses needed for an anxiolytic effect were not associated with sedation. In rodents, there was at least a factor of 10 between anxiolytic doses and doses with mild signs of sedation. In summary, imepitoin showed similar anxiolytic activities as benzodiazepines but without producing the known adverse reactions of benzodiazepines such as sedation.